Mediatisasi Aksi Massa Islam 2 Desember 2016 - Meistra Budiasa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. action Islamic Bela December 2, 2016 was the largest mass action after May 1998. The protesters demanded that Jakarta Governor Basuki Tjahja Purnama (Ahok) convicted and imprisoned because they have insulted the holy verses of the Koran. In this action the mass of worshipers for Friday prayers along the main streets of Jakarta and is centered at the National Monument (Monas). The events of mass action and the Ahok issues like reviving the use of ethnic and religious issues during the New Order is used by the government to maintain power. Islam used to exclude groups considered left and assimilation of Chinese culture performed for suspected links to the event 65. This paper to see how mediatisasi using the politics of fear and how the construction of a mass media reported the action of December 2, 2016.